2022
DOI: 10.1186/s12889-022-13549-3
|View full text |Cite
|
Sign up to set email alerts
|

Health care seeking in modern urban LMIC settings: evidence from Lusaka, Zambia

Abstract: Background In an effort to improve population health, many low- and middle-income countries (LMICs) have expanded access to public primary care facilities and removed user fees for services in these facilities. However, a growing literature suggests that many patients bypass nearby primary care facilities to seek care at more distant or higher-level facilities. Patients in urban areas, a growing segment of the population in LMICs, generally have more options for where to seek care than patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Limitations also exist in several other variables. Travel time was based on the nearest public hospital, whereas in reality, women often bypass the nearest facility 44 45. Further, we made assumptions about travel speed, which may not hold true in all places and might have a larger margin of error within cities due to, for example, variability in traffic and weather, and waiting time 46.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations also exist in several other variables. Travel time was based on the nearest public hospital, whereas in reality, women often bypass the nearest facility 44 45. Further, we made assumptions about travel speed, which may not hold true in all places and might have a larger margin of error within cities due to, for example, variability in traffic and weather, and waiting time 46.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published study based on PVS from 14 high, middle and low income countries showed that the use of secondary or higher facilities as usual source of care was among the highest in Lao PDR [ 36 ]. Furthermore, similar to Zambia, where a recent study identified high rates of bypassing of primary care [ 37 ], Lao PDR has weak gate-keeping policies and allows people to directly access specialists in hospitals [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spatial access has been the primary access challenge in studies examining subjects such as cervical cancer screening in Nigeria [ 28 ], contraceptive use in the Democratic Republic of Congo [ 29 ], and emergency care in Bangladesh [ 30 ]. However, human resources were shown to be the primary constraint in surgical access in Ghana and non-emergency care in Zambia [ 31 , 32 ]. This variation in the cause of access challenges shows the necessity of location-specific and (potentially) service-specific analyses for determining how best to improve health care access in a targeted manner.…”
Section: Discussionmentioning
confidence: 99%